Digital faces of collections - Szala, Marcin (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article describes the methods of antique Library's collections digitization in the center of which the library's object is placed and which respects the features it has in common to the object type, as well as with respect to the unique features of the given copy. It also focuses on the fact that nowadays it is the diversity of the object's forms that makes up the basis for the standards of conduct, i.e. for the selection of methods and parameters of digitization as well as for modes of presenting them online.
Keywords: digitization; library resources; online access; digital library